Creative Empowerment of Inmates: Batik and Merchandise Training for Economic Independence at Class II.B Prison Probolinggo - Moh. Idil Ghufron; Achmad Febrianto (GUYUB: Journal of Community Engagement, 2025)
The high recidivism rate in Indonesia indicates a strong correlation between economic pressure, social inequality, and the lack of skills among inmates, which contribute to repeated criminal behavior. This community engagement program aims to empower inmates through the Asset-Based Community Development (ABCD) approach, which focuses on utilizing community assets and potential to enhance skills and economic independence. The program is implemented in collaboration with various stakeholders, including Batik Ronggomukti and the Office of Cooperatives, Micro Enterprises, Trade, and Industry (Dinas Koperasi, Usaha Mikro, Perdagangan, dan Perindustrian – DKUPP) of Probolinggo Regency. The mentoring activities in this program consist of three main stages: (1) training in batik-making and merchandise production, (2) facilitating stakeholder involvement in skills development and product marketing, and (3) developing marketing strategies to establish a sustainable economic system. This program aims to enhance inmates' entrepreneurial skills, expand business networks with external partners, and reduce the social stigma often faced by former inmates. The implementation of this program has yielded significant outcomes, including the creation of more than 150 creative products with market value at local and national levels, as well as the establishment of five independent business groups among inmates. Additionally, there has been a 30% increase in participants' interpersonal skills and motivation, along with a 25% improvement in their readiness for social reintegration. The program's success has been supported by active stakeholder participation, consistent inmate engagement, and the continuous commitment of various partners in the rehabilitation and economic empowerment of inmates.